Indium silicate with an imandrite-type structure. Issue 20 (26th April 2022) - Ferdov, Stanislav; Shivachev, Boris; Titorenkova, Rositsa; Petrova, Nadia; Tarassov, Mihail; Nikolova, Rositsa
Abstract : This work reports the synthesis and characterization of novel zeolite-like indium silicate MS-2 (Minho-Sofia, solid number 2). Abstract : This work reports the synthesis and characterization of novel zeolite-like indium silicate MS-2 (Minho-Sofia, solid number 2). The structure of this material is analogous to that of the mineral imandrite (Na6 Ca1.5 FeSi6 O18 ), with In instead of Fe in the octahedral position. MS-2 is the first structurally confirmed indium silicate prepared under mild hydrothermal conditions and the only synthetic indium silicate related to the lovozerite mineral group. MS-2 (Na6.23 Ca1.62 In0.68 Si6 O18 ) exhibits significant indium deficiency in the octahedral position thus having the highest Si/In (8.8) ratio among the known indium silicates. The framework consists of occupationally disordered InO6 octahedra interconnected by 6-membered rings of [Si6 O18 ] tetrahedra. The three-dimensional (3D) tunnel system is occupied by Na + and Ca 2+ charge-balancing ions. The low framework density (16.2 FC/1000 Å 3 ) and high thermal stability (up to 900 °C) are comparable to other molecular sieves.